Positioning Coverage Mismatch In Ontology Integration For Owl-Based Ontology - Kasmuri, Emaliana; Woods, Peter (2011)
Many challenges are to be addressed when it comes to integrating ontologies. The common challenges are ontology mismatches. It is important for the integrated ontology to model the intended meaning and resolve all the conflicts so that it will not form a false commitment to the system. Much work has paid attention to finding similarities between ontologies. Little work has considered overcoming coverage mismatch, to solve non-existent concepts, the same concepts being defined differently, and differences in hierarchical structure. This paper identifies, analyzes and models coverage mismatches, filling that gap using OWL ontology. This work is an enhancement to the current findings of ontology mismatch.